The Spatial Rhythm of Fluid Architecture: A Study on the Design Thinking and Aesthetics Composition of BMW Welt in Munich, Germany - Hsu, Hao-Long; Chang, Yu-Li; Lin, Hsiu-Hui (Advances in Social Sciences Research Journal, 2025)
The Austrian architectural team Coop Himmelb(l)au conveys the fluid meaning of architecture through innovative forms inspired by dynamic cyclones, transforming architecture into a dynamic and engaging narrative system that drives the passion for life and the spatial appeal. The design of BMW Welt embodies the whimsical and imaginative qualities of dynamic architecture, creating a sensorially vibrant aesthetic experience through the design syntax and compositional aesthetics of fluid architecture. This research through the methods of literature review and field investigation to analyze Coop Himmelb(l)au's architectural design methods. Taking Noble Schulz's theory of Genius Loci as the framework and theoretical basis of analysis, it analyzes the composition method and design mode of the architectural design. The research found that BMW Welt designed by Coop Himmelb(l)au has the following compositional characteristics: A. The design method of the rhythm of the fluid architectural space composition; B. The self-evident and pioneering characteristics of the automotive dynamic art venue; C. The innovative design methods and characteristics of the exhibition and interior space; D. The innovative dimension of art and emotional architectural experiments. Through the combination of architecture and mobile space atmosphere, shape the architectural contagious car fluid image and the new spiritual aesthetics experience of mobile life.